Deformation Mechanisms in Compositionally Complex Polycrystalline CoNi-Base Superalloys: Influence of Temperature, Strain-Rate and Chemistry - Bezold, Alexander; Freund, Lisa; Förner, Andreas; Völkl, Johannes; Huber, Laura-Kristin; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Recent studies revealed the excellent high temperature properties of polycrystalline CoNi-base superalloys. However, their underlying deformation behavior has been reported only scarcely so far. In this work, the deformation mechanisms of four polycrystalline compositionally complex CoNi-base superalloys with slightly varying chemical compositions were investigated by compression and creep experiments at temperatures between 750 degrees C and 850 degrees C and strain-rates between 10 (3) and 10 (8) s(-1). In the two (Ta + Ti)-rich alloys, a transition of the deformation mechanism from shearing by APB-coupled dislocation pairs to stacking fault shearing and finally also to microtwinning is observed with decreasing strain-rate and increasing temperature. In contrast, APB-based shearing mechanisms represent the dominant mechanism in both (Al + W)-rich alloys in all conditions. At high temperatures and low strain-rates, dislocation glide-climb processes also contribute to plastic deformation in all alloys. By correlating the underlying defect structures with the mechanical properties of these alloys, it becomes evident that a transition to stacking fault shearing and microtwinning leads to a lower strain-rate dependency and superior high-temperature strength in comparison with APB-based mechanisms. Reasons for the different deformation mechanisms, the influence of segregation processes, the consequences for mechanical properties and implications for a mechanism-based alloy design are discussed.
CRIS-Team WoS Importer:2023-01-06

The Effect of Alloying on the Thermophysical and Mechanical Properties of Co–Ti–Cr-Based Superalloys - Zenk, Christopher; Volz, Nicklas; Bezold, Andreas; Huber, Laura-Kristin; Eggeler, Yolita; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Springer International Publishing, 2020)
The system Co–Ti–Cr was recently identified as a very promising base for low mass-density Co-based superalloys. This study presents the influence of quaternary alloying additions on the thermophysical and mechanical properties of a Co–11Ti–15Cr model superalloyModel superalloy. Al, Ta, Re, and W were selected as a starting point for alloy developmentAlloy development as they represent important alloying elements in both Ni-based and Co–Al–W-based superalloys. Microstructure analysis reveals that the addition of only 1 at.% of either of these elements causes the formation of different undesired intermetallic phases in addition to γ and γ′ phases, which is in agreement with thermodynamic calculations. However, a diffusion couple between the Co–Ti–Cr and a Co–Al–W–Ta alloy suggests that the tolerance for alloying elements without destabilizing the γ/γ′ two-phase microstructure is higher when they are present in a certain ratio. Energy-dispersive X-ray spectroscopy shows that Cr and Re are enriched in the γ phase, whereas Ti and W preferentially partition to γ′. All alloying elements increase the yield strength at room temperature, but are disadvantageous at 1000 °C. Re and W retain their strengthening effect up to 900 °C.